2014
DOI: 10.1016/j.vetmic.2013.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of influenza A virus from captive wild boars in Brazil reveals a human-like H1N2 influenza virus

Abstract: Influenza is a viral disease that affects human and several animal species. In Brazil, H1N1, H3N2 and 2009 pandemic H1N1 A(H1N1)pdm09 influenza A viruses (IAV) circulate in domestic swine herds. Wild boars are also susceptible to IAV infection but in Brazil until this moment there are no reports of IAV infection in wild boars or in captive wild boars populations. Herein the occurrence of IAV in captive wild boars with the presence of lung consolidation lesions during slaughter was investigated. Lung samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Argentina also reported distinct human seasonal 1B.2 viruses (Pereda et al 2011). In Brazil, H1N2 viruses with H1 HA and N2 NA genes of human seasonal origin and internal genes from H1N1pdm09 were similarly detected (Biondo et al 2014), followed by detection of an additional lineage of H1N2 reassortants with the H1N1pdm09 internal genes and human seasonal surface genes (Nelson et al 2015b). Chile reported two human seasonal lineage H1 viruses paired with N1 or N2 NAs that are each distinct from those found in other South American countries (Nelson et al 2015a).…”
Section: Bmentioning
confidence: 98%
“…Argentina also reported distinct human seasonal 1B.2 viruses (Pereda et al 2011). In Brazil, H1N2 viruses with H1 HA and N2 NA genes of human seasonal origin and internal genes from H1N1pdm09 were similarly detected (Biondo et al 2014), followed by detection of an additional lineage of H1N2 reassortants with the H1N1pdm09 internal genes and human seasonal surface genes (Nelson et al 2015b). Chile reported two human seasonal lineage H1 viruses paired with N1 or N2 NAs that are each distinct from those found in other South American countries (Nelson et al 2015a).…”
Section: Bmentioning
confidence: 98%
“…The first report on the isolation of SIV from oral cavity of naturally infected swine occurred in the state of São Paulo only in 2006 (Mancini et al, 2006). Recent studies have identified the SIV in industrial and wild pig herds (Biondo et al, 2014;Schaefer et al, 2015). Thus, a study performed in 48 intensive pig farms in the southern region, found that around 30 % of them had 95 % of positive animals, resulting in a total animal level prevalence of 78.1 %, suggesting that the disease might be widespread in some Brazilian regions (Ciacci-Zanella et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the reported wild boar virus infections, such as HEV, PoR-VA, and porcine influenza A virus are known to infect other animal species and are considered important zoonotic diseases (Ruiz-Fons et al 2008, Meng et al 2009, Okadera et al 2013, Biondo et al 2014. Therefore, the potential risks of disease transmission among wild animals and livestock and/or the human population cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Wild boars are susceptible to infections by viruses that also affect domestic pigs (Sus scrofa domesticus), such as porcine group A rotavirus (PoRVA), porcine circovirus type 2 (PCV2), hepatitis E virus (HEV), Aujeszky disease virus (ADV), porcine parvovirus (PPV), porcine reproductive and respiratory syndrome virus (PRRSV), classical swine fever virus (CSF), torque teno sus virus (TTSuV), influenza A virus, and others (Ruiz-Fons et al 2008, Meng et al 2009, Okadera et al 2013, Biondo et al 2014. These animals are also susceptible to infections by PTV, PSV, and EV-G, which were described in asymptomatic wild boars in Hungary (Boros et al 2012a, Boros et al 2012b, Spain (Cano--Gómez et al 2013), and the Czech Republic (Prodělalová 2012).…”
Section: Introductionmentioning
confidence: 99%